Gendered Choices: Examining the Mechanics of Mobile and Online Girl Games. (January 2018) - Cummings, Kelsey
This article analyzes girl games, a subgenre of casual mobile and online games created and marketed for preteen girls. Through an examination of Barbie Fashionistas, Style Studio: Fashion Designer, and Central Park Wedding Prep, all of which are representative of traditional dress-up and makeover-oriented girl games, I explore how seemingly broad mechanics-based choices available to players within the games reinforce and respond to patriarchal ideologies, and argue that the mechanics of mobile and online girl games serve gendered and neoliberal ends both in game and in the larger context of North American gaming culture. Conducting close readings on and accounting for the mechanics of an understudied genre within the field to advocate for greater study of both game mechanics and girl games, I demonstrate how the availability of choice intrinsic in girl games provides opportunity to explore how players are constructed as neoliberal subjects.